A virtual reality system for pain and anxiety management during outpatient hysteroscopy—A randomized control trial. (23rd November 2021) - Fouks, Yuval; Kern, Guy; Cohen, Aviad; Reicher, Lee; Shapira, Ziv; Many, Ariel; Yogev, Yariv; Rattan, Gilad
Abstract: Background: Visual and acoustic virtual reality (VR) has been increasingly explored as a non‐pharmacological tool for pain relief in clinical settings. Objective: We aimed to evaluate the effectiveness of VR as a distraction technique in the management of acute pain during operative hysteroscopy in the outpatient setting. Methods: A prospective, open‐label, randomized control trial in a tertiary university‐affiliated medical centre between April and August 2020. Overall, 82 women were randomly allocated to undergo operative hysteroscopy either with the use of VR ( n = 44, study group) or with standard treatment (control group, n = 38). VR was applied throughout the procedure and no anaesthesia was given. The primary outcome measures included self‐reported intraoperative pain. Other objectives included vital parameters as pulse rate (PR) and respiratory rate (RR) before and during the first 3 min of the procedure. Pain and anxiety outcomes were measured as numeric rating scores. Results: The baseline parameters were similar between groups. The mean duration for the procedure was 8.1 ± 3.2 vs. 7.3 ± 6.0 min for the study and the control groups ( p = 0.23). There were no statistically significant differences between the reported pain scores during the procedure [median (interquartile range) 5.0 (3.0–7.2) vs. 5.0 (3.0–8.0), respectively; p = 0.67]. While neither intraoperative heart rate nor respiratory rate differed between groups [14.0 (13.0–16.0) vs. 14.0 (11.0–16.5); p = 0.77)], the increase of heart rate was found greater in the VR group [+7.0 (8.5) vs. +1.0 (12.2); p = 0.01]. Conclusion: VR was not effective in reducing pain during an outpatient operative hysteroscopy. Significance: The use of a Virtual reality system was found ineffective in reducing pain during and after an office operative hysteroscopy without anaesthesia, in a thorough examination of both continuous physiological parameters and women's self‐reported measures.